Field Performance and Susceptibility to Fungal Pathogens of Eleven Blackberry Cultivars. (14th September 2020) - Lawrence, Brian T.; Melgar, Juan Carlos; Dallmann, Marcie J.; Ouellette, David R.; Hu, Mengjun; Schnabel, Guido
ABSTRACT: Horticultural performance of eleven blackberry cultivars, including two primocane-fruiting cultivars, was evaluated over three years after fruiting began at the Musser Fruit Research Center in South Carolina, United States. Results showed differences in yield between cultivars for each year of the study. 'Natchez' had the highest cumulative yield after three years, followed by 'Navaho', 'Von', and 'Osage', whereas 'Prime-Ark® Traveler' produced significantly less than these four cultivars. Yield steadily declined for all cultivars over the three years, except for 'Osage', which remained consistent. 'Prime-Ark® Freedom' always had the largest fruit, although it had the greatest yield reduction after the second year. Multiple factors may explain yield decline for the majority of the cultivars studied, including freeze damage and tip dieback. Tip dieback was observed in 2016 in multiple cultivars, but dieback incidence was highest on 'Prime-Ark® Traveler'. The dieback was associated with an outbreak of broad mites and thrips in the experimental block and with secondary pathogens isolated from the decaying tissues primarily Fusarium spp. and Alternaria spp. Cultivar differences in susceptibility to Alternaria spp. were confirmed in laboratory studies.